Velocity-Dependent Nucleon-Nucleon Potentials - Bhaduri, Rajat K. (My University, 1963)
An investigation is carried out to see whether a nonsingular two-nucleon velocity-dependent potential can give similar results as those of a model hard-core potential in the a-state in nuclear-matter. Reasons for failure of some earlier velocity-dependent model potentials to give saturation in nuclear-matter at reasonable densities are examined and a new velocity-dependent potential is proposed which gives results similar to the model hard-core potential.
Keywords: nonsingular two-nucleon velocity-dependent potential; nuclear-matter; hard-core potential